Axillary artery injury combined with delayed brachial plexus palsy due to compressive hematoma in a young patient: a case report - Murata, Keiichi; Maeda, Manabu; Yoshida, Atsushi; Yajima, Hiroshi; Okuchi, Kazuo (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Introduction Axillary artery injury in the shoulder region following blunt trauma without association with either shoulder dislocation or fracture of the humeral neck has been previously reported. Axillary artery injury might also be accompanied with brachial plexus injury. However, delayed onset of brachial plexus palsy caused by a compressive hematoma associated with axillary injury after blunt trauma in the shoulder region has been rarely reported. In previous reports, this condition only occurred in old patients with sclerotic vessels. We present a case of a young patient who suffered axillary artery injury associated with brachial plexus palsy that occurred tardily due to compressive hematoma after blunt trauma in the shoulder region without association of either shoulder dislocation or humeral neck fracture.Case presentation A 16-year-old male injured his right shoulder in a motorbike accident. On initial physical evaluation, the pulses on the radial and ulnar arteries in the affected arm were palpable. Paralysis developed later from 2 days after the injury. Functions in the right arm became significantly impaired. Angiography showed complete occlusion of the axillary artery. Magnetic resonance imaging demonstrated a mass measuring 4 × 5 cm that was suspected to be a hematoma compressing the brachial plexus in a space between the subscapular muscle and the pectoralis minor muscle. Surgery was performed on the third day after injury. In intraoperative observations, the axillary artery was occluded with thrombus along 5 cm; a subscapular artery was ruptured; the brachial plexus was compressed by the hematoma. After evacuation of the hematoma, neurolysis of the brachial plexus, and revascularization of the axillary artery, the patient had an excellent functional recovery of the affected upper limb, postoperatively.Conclusion Surgeons should be aware that axillary artery injuries may even occur in young people after severe blunt trauma in the shoulder region and can be associated with secondary brachial plexus injury due to a hematoma. For treatment in cases with progressive nervous deficit after trauma, not only reconstruction of the injured artery but also immediate evacuation of the hematoma, and exploration of the brachial plexus are necessary to avoid irreversible neurological damage.